The creation of a Polish community in the Vaal Triangle, South Africa 1980-1989 - van Ingen-Kal, Michaela; Macqueen, Ian (Contree, 2025)
During the 1980s, amid a domestic crisis, almost a million Poles left their homeland, fleeing a failing socialist economy and a repressive regime. The majority settled in Western Europe, Scandinavia and the United States of America, but some elected to relocate to South Africa. Drawing on Everett Lee’s ‘push and pull theory’, firstly, this article examines factors influencing the migration of Poles to South Africa. Secondly, it examines the formation of a Polish community in the Vaal Triangle and the importance of religion in consolidating the community and preserving a sense of Polish culture. By focussing on the Vaal Triangle during the 1980s, an area that attracted a proportionally higher number of Polish immigrants than other parts of the country, the article addresses the significance of its state industries as a magnet for skilled immigrants. Contribution The article draws on South African newspaper coverage of Poland’s crisis as a comparative lens, together with interviews with members of the Polish community in South Africa and archival research.